One piece at a time : Adding to the puzzle of S0 formation - Escudero, Carlos Gabriel (2017)
Understanding the origin of galaxies remains a topic of debate in the current astronomy. In this work, we have focused on lenticular (S0) galaxies located in low-density environments, using their associated globular cluster (GC) systems as a tool. Initially, we have started the study of three S0 galaxies-NGC 2549, NGC3414 and NGC5838-using photometric data in several filters obtained with the GMOS camera mounted on the Gemini North telescope. The different GC systems, as well as their host galaxies, have shown particular features, such as multiple GC subpopulations and low-brightness substructures. These pieces of evidence show that the mentioned galaxies have suffered several merger/interaction events, even the accretion of satellite companions, probably causing their current morphologies.